PENGARUH DAYA TARIK IKLAN DAN PERILAKU ZAPPING TERHADAP EFEKTIVITAS PERIKLANAN MEDIA VISUAL TELEVISI (Studi Empiris Pada Mahasiswa Universitas Stikubank Semarang Angkatan 2010) - Evi Shofia Inayati, 10.05.51.0087 (Students Journal of Economic and Management, 2014)
This study is examines the effect of the attraction advertising and zapping behavior effectiveness of visual media advertising (television. )Society in this era more happy to use the gadget than see television, Which result in declining communities close attention to advertising on telivision. When the people watching of television their tend to zap a commercial break (Zapping), itâs not uncommon of them do not pay attention to the appeal of ads served and even avoid to see the other channel. The attraction advertising and zapping behavior that will be used to effect the advertising effectiveness.In this study researcher used purposive sampling tekhnik to obtain a sample of student of Universitas Stikubank Semarang, and the sample size is 86 students. Students later in the test data using by SPSS 20 and the validity of the questionnaire in this thesis is valid. Based on the indicators used reliability test is an indicator of the variabels, the result is advertising effectthe attractiveness positively and significantly to effectiveness of advertising while zapping behaviors negatively affect the effectiveness of advertising, which means more requent television viewewrs switched channels television advertising effectiveness rat will dicline.This study has limitation that sampling periods were relatively short, it has not considered yet main control variabel and other variabels that could influence the effectiveness of advertising Therefore, further research is recommended to consider the main variabels and another control variabels as wel as the need for longer periods of study that may in generalisation. Keywords: Attraction advertising, zapping behaviors, effectivrness of visual media advertising